Microbiology literacy and its influence on knowledge, perceptions and community attitudes - Mustofa, Ali; Hastuti, Utami Sri; Susanto, Hendra (Universitas Negeri Jakarta, 2025)
Microbiology literacy development shapes people's attitudes, behaviors, and perceptions toward microorganisms. This study aims to explore the relationship between microbiological literacy and people's perceptions and attitudes towards microorganisms. This study uses the Systematic Literature Review (SLR) method to analyze the relationship between microbiological literacy and public knowledge, attitudes, and perceptions of microorganisms. Data were retrieved from Scopus using relevant keywords and then filtered based on the following criteria: published between 2019–2024, in English, and open access. The analysis was conducted through four steps: coding, concept review, and summarizing key information (author, year, and core concepts). The results were synthesized to map the relationship between microbiological literacy and public perceptions. The results showed that respondents' knowledge levels varied about various health issues. Good microbiological knowledge can improve health literacy, affecting individual attitudes and perceptions of health. Regarding respondents' attitudes, it is known that respondents are interested in education and health awareness. A positive attitude toward health can encourage actions that support public health. In contrast, individuals with low microbiology knowledge orientation are more likely to cause negative perceptions and distrust of health interventions. Continuous, evidence-based education is essential to improve microbiology and health literacy and shape positive attitudes toward health interventions. Microbiology knowledge has a broad impact on daily life and the future. However, there are significant challenges in understanding microbiology. Public perception of microbes is often only associated with 'germs' and negative images. Therefore, microbiology knowledge in learning must be presented in visual arts and visual, olfactory, and tactile experiences. The more we understand the role and knowledge of microbes, the better we can make relevant decisions.